Roman pottery in the Near East : local production and regional trade : proceedings of the Round Table held in Berlin, 19-20 February 2010 - Fischer, Bettina,; Gerber, Yvonne,; Hamel, Hanna, (Roman and late antique Mediterranean pottery ;, 2014)
Discussions and scientific exchange are crucial for the advancement of a young discipline such as the study of Roman pottery in the Near East. Therefore, in addition to large conferences such as the 'Late Roman Coarse Ware Conference' (LRCW) where the Near East plays only a marginal role, an international workshop with 20 participants dedicated solely to the study of Roman common ware pottery in the Near East was held in Berlin on 18th and 19th February 2010. The goal of this workshop was to provide researchers actively engaged in the study of Roman common wares the possibility to meet and discuss the current state of research as well as questions and problems they are facing with their material. This volume presents 17 papers from this event.